Pulping Of Vetiver Grass With NH4OH-KOH-AQ Mixtures - Panitnad Chandranupap; Pravitra Chandranupap (ASEAN Journal of Chemical Engineering, 2012)
The aim of this work was to study the effects of various experimental parameters on vetiver grass (Vetiveria nemoralis A. Camus) pulping. Mixtures of NH4OH-KOH were used as cooking liquors. The caustic potash did not only reduce the NH3 usage and cooking time, but also provided a potassium source as a fertilizer in the black liquor. Anthraquinone (AQ) was added in certain amount as cooking catalyst. The experiment was conducted following a central composite design involving three pulping variables (amount of KOH: 3.5 to 7% on oven-dried sample, amount of NH4OH : 25 to 45% on oven-dried sample, and cooking temperature : 145 to 160°C). The quantity of anthraquinone was fixed at 0.1% on oven-dried sample. Pulping time was fixed at 2 hours and liquid-to-oven-dried sample ratio was 8:1. Responses of pulp properties to the process variables were analyzed using DESIGN-EXPERT®, a computer-aided design of experiment software. The pulp properties revealed that this pulp is capable for making of printing and writing paper. Furthermore, this study provided a new pulping process for vetiver grass to reduce problems of discharge black liquor.